A Non-invasive Real-Time Methodology for the Quantification of Antioxidant Properties in Coffee During the Roasting Process Based on Near-Infrared Spectroscopy - Catelani, Tiago A. [UNESP]; Páscoa, Ricardo N. M. J.; Santos, João Rodrigo; Pezza, Leonardo [UNESP]; Pezza, Helena R. [UNESP]; Lima, José L. F. C.; Lopes, João A. (Springer Nature, 2017)
This paper describes the development of a real-time method based on near-infrared spectroscopy (NIRS) for determination of total antioxidant capacity (TAC) and total phenolic content (TPC) in coffee during the roasting process. The real-time non-invasive monitoring procedure involved pointing a diffuse reflectance probe directly at the roasting chamber through a glass window in order to monitor the roasting process. The figures of merit of the chemometric models to estimate TAC and TPC showed selectivity values higher than 12% and determination coefficients (R2 P) above 0.90. The TAC and TPC profiles during the roasting procedure are discussed in terms of the antioxidant compounds likely to be present in green and roasted coffee. NIRS was found to be a satisfactory real-time tool for monitoring the content of antioxidant compounds in coffee during the roasting process, complementing other established procedures.
Keywords: Coffee roasting; Near-infrared spectroscopy; Real-time monitoring; Total antioxidant capacity; Total phenolic content